Near-IR mediated intracellular uncaging of NO from cell targeted hollow gold nanoparticles. Issue 100 (21st October 2015) - Levy, Elizabeth S.; Morales, Demosthenes P.; Garcia, John V.; Reich, Norbert O.; Ford, Peter C.
Abstract : NIR light triggers NO delivery with unprecedented spatio-temporal control inside prostate cancer cells from surface-modified hollow gold nanoshells. Abstract : We demonstrate modulation of nitric oxide release in solution and in human prostate cancer cells from a thiol functionalized cupferron (TCF) absorbed on hollow gold nanoshells (HGNs) using near-infrared (NIR) light. NO release from the TCF–HGN conjugates occurs through localized surface heating due to NIR excitation of the surface plasmon. Specific HGN targeting is achieved through cell surface directed peptides, and excitation with tissue penetrating NIR light provides unprecedented spatio-temporal control of NO delivery to biological targets.